Early mucosal responses in common carp (Cyprinus carpio) to the infection of Aeromonas hydrophila - Jiali Wang; Qi Zhou; Hongyu Zhang; Yanliang Jiang (Aquaculture Reports, 2024)
Common carp (Cyprinus carpio), an economically important freshwater fish species, is worldwide farmed especially in Europe and Asia. The current high-density intensive rearing way leading to a high susceptibility to various pathogens, and Aeromonas hydrophila is one of the most frequently encountered bacteria, causing huge economic losses to the common carp industry. The mucosal barrier of fish constitutes the first line of defense against various pathogens, and some level of inter-connectivity exists among teleost mucosal tissues. However, the molecular basis for a common mucosal immune response at multiple sites or response at one site but during different timepoints following stimulation remains to be studied. In this study, we examined and systematically analyzed a total of 144 transcriptome files from three primary common carp mucosal tissues at four early timepoints following the infection of A. hydrophila. A total of 410 unigenes were significantly differentially expressed in all tested mucosal tissues. Through GO enrichment and KEGG pathway analysis, 28 key genes which might played critical roles in the common mucosal immune response of common carp during the early stage of bacterial infection were identified. Further WGCNA analysis showed that, besides the common response, three mucosal tissues exhibited tissue-specific gene regulatory network. Meanwhile, candidate hub genes in each tissue were identified, including trim3, rpl14, tln2, itpr1, and others. Our results will provide a fundamental basis for understanding the molecular mechanisms of teleost mucosal immunity, and might suggest strategies for developing novel teleost mucosal vaccines in aquaculture.